Proceedings of the 2015 Symposium and Bootcamp on the Science of Security 2015
DOI: 10.1145/2746194.2746197
|View full text |Cite
|
Sign up to set email alerts
|

Towards a science of trust

Abstract: It is unclear how to think about trust or to model its ebb and flow. Is there some sort of Second Law of Thermodynamics of trust, where trust starts high and is dissipated over time? Or is it the contrary, that trust starts low and can grow through a series of good experiences?Is it more complex, and how can the waxing and waning be thought about? JASON Report on Science of Cyber-Security [17] AbstractThe diverse views of science of security have opened up several alleys towards applying the methods of science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Nonetheless, proving the absence of failure modes or the presence of security properties is an important part of cryptography, formal methods, etc. (8)…”
Section: Other Approaches To Securitymentioning
confidence: 99%
“…Nonetheless, proving the absence of failure modes or the presence of security properties is an important part of cryptography, formal methods, etc. (8)…”
Section: Other Approaches To Securitymentioning
confidence: 99%
“…The practice is far ahead of theory. The research reported in this paper is a part of a broader effort [9,31,33,34,47] towards developing models, methods, and tools for this area, where human and computational behaviors are not just inseparable, but they determine each other; and they do not just determine each other, but they seek to control each other.…”
Section: Causal Cognition As a Security Problemmentioning
confidence: 99%
“…I N the past decade there has been significant effort in adding formal underpinnings to security [1], [2]. This research trajectory is evidenced by the NSF/IARPA/NSA workshop on the science of security, which underlines that there are three areas in need of innovation: metrics, formal methods, and experimentation [3].…”
Section: Introductionmentioning
confidence: 99%